28 GHz Wireless Backhaul Transceiver Characterization and Radio Link Budget. Issue 1 (15th February 2018) - Leinonen, Marko E.; Destino, Giuseppe; Kursu, Olli; Sonkki, Marko; Pärssinen, Aarno
Abstract : Millimeter wave communication is one of the main disruptive technologies in upcoming 5G mobile networks. One of the first candidate applications, which will be commercially ready by 2020, is wireless backhaul links or wireless last mile communication. This paper provides an analysis of this use‐case from radio engineering and implementation perspectives. Furthermore, preliminary experimental results are shown for a proof‐of‐concept wireless backhaul solution developed within the EU‐KR 5GCHAMPION project, which will be showcased during the 2018 Winter Olympic Games in Korea. In this paper, we verify system level calculations and a theoretical link budget analysis with conductive and radiated over‐the‐air measurements. The results indicate that the implemented radio solution is able to achieve the target key performance indicator, namely, a 2.5 Gbps data rate on average, over a range of up to 200 m.